Comparative Study on Torsional Shear and Triaxial Test of Asphalt Mixtures - Jun Xie; Yifan Wang (Advances in Civil Engineering)
In order to verify the reliability and effectiveness of the torsional shear test method, a comparative study of the torsional test under normal stress conditions and triaxial test was carried out with two different asphalt types (unmodified asphalt and SBS-modified asphalt) for asphalt mixtures of AC-13 and AC-20 at three temperatures of 20°C, 40°C, and 60°C. The results showed that the crack spreading routine and the spreading angle were different between the two test methods. The cohesion of the torsional test was slightly larger than that of the triaxial test for different mixtures, asphalts, and temperatures. The main cause of this result is the difference of loading mode. The internal friction angle was basically equivalent in the two methods for different mixtures, asphalts, and temperatures, which indicated that the internal friction angle was mainly related to the spatial distribution of the aggregates or the mutual interlock and had little to do with the test method and external conditions. The results of the ANOVA and regression analysis indicated that the two test methods have a good correlation, and the torsional shear test is a reliable and effective laboratory test method for evaluating the shear performance of asphalt mixtures.